PENGENDALIAN Piper yellow mottle virus (PYMoV) PADA TANAMAN LADA DENGAN MENGGUNAKAN MIKORIZA - Trisnani Alif; Yustika Aulia Rahma; Nur Habibatur Rohma (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Disease caused by Piper yellow motle virus (PYMoV) is an important disease in pepper plants. Mycorrhizal fungus inoculation can delay PYMoV infection and delay the appearance of mottling symptoms in pepper plants. This study aims to control PYMoV pathogens in pepper plants using mycorrhizal fungi. The design of this study used a completely randomized design with 3 treatments. The results showed that the dose of 15 g had the lowest disease intensity. Also, the best mycorrhizal fungal infection and mycorrhizal fungal population were found at a dose of 15 g.